A Prospective Study of Serum IL-15, TNF-α, and YKL-40 as Predictors of Knee Osteoarthritis Progression: Serum IL-15, TNF-α, and YKL-40 in Osteoarthritis - Wu, Zungui; Liu, Yu; Xie, Peigeng; Xiong, Chunxiang (Journal of Medical Biochemistry, 2026)
Objective: To investigate the prognostic value of serum Interleukin-15 (IL-15), Tumour Necrosis Factor-alpha (TNF-α), and Chitinase-3-like protein 1 (YKL-40) for predicting structural and clinical progression in knee osteoarthritis (OA). Methods: In a 36-month prospective cohort study, 320 participants with symptomatic knee OA (Kellgren-Lawrence [KL] grade 2-3) were assessed. Baseline serum biomarkers were quantified via high-sensitivity ELISA. Primary outcome was radiographic progression (increase in KL grade ≥1 or joint space narrowing [JSN] ≥0.5mm). Secondary outcomes included clinically important worsening in WOMAC pain (≥20%) and incidence of total knee arthroplasty (TKA). Results: Elevated baseline levels of IL-15, TNF-α, and YKL-40 were independent predictors of radiographic progression after multivariate adjustment (IL-15: OR 2.41, 95% CI 1.52–3.81; TNF-α: OR 2.08, 1.31–3.30; YKL-40: OR 2.85, 1.81–4.49). A composite High-Risk Inflammatory Phenotype (HRIP), defined as elevation in ≥2 biomarkers, demonstrated superior predictive capacity (OR 5.12, 3.02–8.68 for radiographic progression; HR 3.45, 1.95–6.10 for TKA). The addition of the HRIP to a clinical model significantly improved predictive discrimination (AUC increase from 0.68 to 0.79, p
Keywords: Osteoarthritis; Biomarkers; Prognosis; Cytokines; IL-15; TNF-α; YKL-40; Inflammation.